Habitat selection in birds feeding on ocean shores: landscape effects are important in the choice of foraging sites by oystercatchers. (29th April 2013) - Schlacher, Thomas A.; Meager, Justin J.; Nielsen, Tara
Abstract Food availability is a fundamental determinant of habitat selection in animals, including shorebirds foraging on benthic invertebrates. However, the combination of dynamic habitats, patchy distributions at multiple spatial scales, and highly variable densities over time can make prey less predictable on ocean‐exposed sandy shores. This can, hypothetically, cause a mismatch between prey and consumer distributions in these high‐energy environments. Here we test this prediction by examining the occurrence of actively foraging pied oystercatchers (Haematopus longirostris) in relation to physical habitat attributes and macrobenthic prey assemblages on a 34 km long, high‐energy beach in Eastern Australia. We incorporate two spatial dimensions: (i) adjacent feeding and non‐feeding patches separated by 200 m and (ii) landscape regions with and without foraging birds separated by 2–17 km. There was no support for prey‐based or habitat‐based habitat choice at the smaller dimension, with birds being essentially randomly distributed at the local scale. Conversely, at the broader landscape dimension, the distribution of oystercatchers was driven by the density of their prey, but not by attributes of the physical beach environment. This scale‐dependence suggests that, on open‐coast beaches, landscape effects modulate how mobile predators respond to variations in prey availability.